Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

My trouble is in finding the solution $u = u(x,y)$ of the semilinear PDE $$x^2u_x +xyu_y = u^2$$ passing through the curve $u(y^2,y) = 1.$

So I started by using the method of characteristics to obtain the set of differential, by considering the curve $\Gamma = (y^2, y, 1)$. I then reparametrize $\Gamma$ by $r\in\mathbb{R}$, as $\Gamma = (r^2, r, 1)$.

Then, to my understanding, I need to solve the set of ODE's $$\frac{dx}{ds}(r,s) = x^2$$ $$\frac{dy}{ds}(r,s) = xy$$ $$\frac{dz}{ds} = z^2$$ with initial conditions $x(r,0) = r^2$, $y(r,0) = r$, and $z(r,0) =r^2$.

And this is where I run into a wall. How can I solve the system of ODE's, when they are in respect to $r$ and $s$? Also, I'm not even sure if I'm going about this in the correct way.

Your thoughts are appreciated, as always. ~Dom

share|cite|improve this question
up vote 1 down vote accepted



Follow the method in

$\dfrac{dx}{dt}=x$ , letting $x(0)=x_0$ , we have $x=x_0e^t$

$\dfrac{dy}{dt}=y$ , letting $y(0)=y_0$ , we have $y=y_0e^t$

$\dfrac{du}{dt}=\dfrac{u^2}{x}=\dfrac{u^2}{x_0e^t}=\dfrac{u^2e^{-t}}{x_0}$ , letting $u(0)=\dfrac{1}{f\left(\dfrac{x_0}{y_0}\right)}$ , we have $u(x,y)=\dfrac{x_0}{x_0f\left(\dfrac{x_0}{y_0}\right)+e^{-t}}=\dfrac{xe^{-t}}{xe^{-t}f\left(\dfrac{xe^{-t}}{ye^{-t}}\right)+e^{-t}}=\dfrac{x}{xf\left(\dfrac{x}{y}\right)+1}$

$u(y^2,y)=1$ :



$\therefore u(x,y)=\dfrac{x}{x\left(1-\dfrac{y^2}{x^2}\right)+1}=\dfrac{x^2}{x^2+x-y^2}$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.